Option D: [tex]4x^{2} +20x-2[/tex] is the value of [tex](c \circ d)(x)[/tex]
Explanation:
Given that the two functions [tex]c(x)=4 x-2[/tex] and [tex]d(x)=x^{2} +5x[/tex]
To find the value of [tex](c \circ d)(x)[/tex]:
The value of [tex](c \circ d)(x)[/tex] can be determined using the formula,
[tex](c \circ d)(x)=c[d(x)][/tex]
First, we shall substitute [tex]d(x)=x^{2} +5x[/tex] in the above formula.
Thus, we have,
[tex](c \circ d)(x)=c[x^2+5x][/tex]
Now, substituting [tex]x=x^2+5x[/tex] in the function [tex]c(x)=4 x-2[/tex], we get,
[tex](c \circ d)(x)=4(x^2+5x)-2[/tex]
Simplifying the terms, we get,
[tex](c \circ d)(x)=4x^2+20x-2[/tex]
Therefore, the value of [tex](c \circ d)(x)[/tex] is [tex]4x^{2} +20x-2[/tex]
Hence, Option D is the correct answer.